The Influence of Internal and Macroeconomic Factors on the Profitability of Islamic Commercial Banks in Indonesia - Aam; Dito Prakoso (SMART Insight, 2021)
This paper analyzes the determinant factors to the profitability of Islamic Commercial Banks in Indonesia during the period 2012 - 2019. To this objection, 14 Islamic Commercial Banks in Indonesia have been studied. A panel data study uses impact of internal bank and macroeconomic are combine to explain the profitability of Islamic Commercial Banks as measured by Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), total of assets, inflation and Gross Domestic Product (GDP). This study analyzed using the Generalized Method of Moments (GMM) dynamic panel data. The results of the study found that only internal bank factors that significantly affect the profitability of Islamic Commercial Banks, namely CAR, NPF, and FDR. CAR has a positive effect on ROA, while FDR has a negative effect on ROA for Islamic Commercial Banks in Indonesia. Only NPF has a negative effect on the two proxies of profitability (ROA and ROE). The results of this study indicate that Islamic Commercial Banks in Indonesia need to manage their assets optimally and apply better prudential principles in financing management to minimize financing risks so as to increase bank profitability.